PENGARUH BIAYA PRODUKSI DAN BIAYA PROMOSI TERHADAP LABA BERSIH PADA CV. NJ FOOD INDUSTRIES - Cut Ana Rohani (Nusantara Hasana Berdikari, 2021)
This research is aim to determine a effect of Production Costs and Promotion Costs On Net Profit in CV. NJ Food Industries. The variables used in this research is Production Costs, Promotion Costs and Net Profit. The sample used in this research is financial statement from year 2018 to 2020 as many as 36 samples. The analysis used in multiple linear regression analysis. The analysis is used to determine the significance either partially or simultaneously. The result of the partial test are (-3,795 < - 2,035) the Ho is rejected and Ha is accepted. And the significant value is 0.001 < 0.05 then Ha is accepted. So it can be said that partially the production costs have a partial and significant effect on net income. From the result of data processing in the table, it can be seen that the tcount variable is -0.522 while the ttable is 2.035 or (-0.522 < -2.036) and the significant value is 0.605 > 0.05. so it can be done that partially romotion costs don’t partially effect net income, meaning Ho is accepted and rejected. Statictical result fcount > ftable 7,279 > 3,28 then Ho is rejected and Ha is accepted. With a significant value of 0.002 < 0.005, production costs and promotion costs have a significant effect on net income.